Penundaan Pemilihan Umum dalam Sistem Ketatanegaraan Indonesia - Srye Micze Ridua; Jemmy Jefry Pietersz; Hendry John Piris (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The 1945 Constitution of the Republic of Indonesia does not regulate the postponement of elections and clearly emphasizes that elections are held once every five years, but the discourse on postponing elections has been discussed in Indonesia. Purposes of the Research: The constitutionality of postponing elections and the legal consequences of postponing elections in the Indonesian constitutional system. Methods of the Research: The research method used is normative juridical with statutory and conceptual approaches.Results of the Research: The results of this study concluded that the postponement of elections can use the form of postponement of subsequent elections in the Election Law because the form of postponement of elections in the Election Law does not conflict with the 1945 Constitution of the Republic of Indonesia. Even though the 1945 Constitution of the Republic of Indonesia has stated that elections are held once every five years, in realizing the postponement of elections there is a constitutional way, namely there is a constitutional mechanism, namely through amendments to the 1945 Constitution of the Republic of Indonesia. The postponement of elections also affects the term of office of the President and Vice President as well as members of the DPR, DPD and DPRD